THERMAL BEHAVIOUR OF POLYURETHANE MATRIX COMPOSITE MATERIALS - TIUC, Ancuţa Elena; NEMEȘ, Ovidiu; PERHAIȚĂ, Ioana; VERMEŞAN, Horaţiu; GABOR, Timea; DAN, Viorel (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This paper describes the thermal behaviour of some composite materials, polyurethane foams reinforced with tire rubber waste and fir sawdust. According to experimental results, TG and DTG plots were drawn for finding the thermal stability domains, the partial and total weight loss and the temperature of the maximum weight loss. Composite materials have superior thermal stability of raw materials from which they were made. Increasing the percentage of polyurethane foam results in greater weight loss front of recycled rubber, but lower than fir sawdust and polyurethane foam.